Do firm’s corporate performance and corporate governance affect the level of earnings management in Taiwan IC design industry? - Ma, Chih-Ting (2010)
Considering the growth potential and profitability of IC design companies in Taiwan, investors have become more interested in this industry. Consequently, the managers of these companies are more concerned about earnings and utilise accounting accruals to manage their earnings. This project uses a modified Jones model to detect earnings management and regression analysis to examine the relationships among earnings management and performance, governance, IPOs, and audit quality in the Taiwanese IC design industry. The results show that earnings management exists in Taiwanese IC design companies. In addition, the level of earnings management is influenced by each firm’s performance, governance, and audit quality. Based on these results, investors should carefully read the financial reports of Taiwanese IC design companies; also, auditors should pay more in-depth attention when auditing these companies. Finally, internal controls should be more effective and capable of preventing earnings management.